Iron overload and chelation modulates bisretinoid levels in the retina - Jin Zhao; Hye Jin Kim; Diego Montenegro; Josh L. Dunaief; Janet R. Sparrow; Janet R. Sparrow (Frontiers in Ophthalmology, 2023)
AimIron dysregulation in conjunction with other disease processes may exacerbate retinal degeneration. We employed models of iron overload and iron chelation to explore the interactions between iron-catalyzed oxidation and photoreactive bisretinoid lipofuscin.MethodsThe mice were injected intravitreally with ferric ammonium citrate (FAC) or were treated using the iron chelator deferiprone (DFP) from birth to 2 months of age. Short-wavelength fundus autofluorescence (SW-AF) and spectral-domain optical coherence tomography (SD-OCT) scans were acquired. The bisretinoid levels were quantified using ultra performance liquid chromatography (UPLC) and in vivo through quantitative fundus autofluorescence (qAF). In histologic sections, the photoreceptor cell viability was assessed by measuring the thickness of the outer nuclear layer (ONL).ResultsThe levels of bisretinoids, all-trans-retinal dimers, and A2PE were significantly increased in the FAC-injected eyes of C57BL/6J mice. Seven days after FAC injection, hyperautofluorescent foci were visible in fundus autofluorescence (488 nm) images, and in SD-OCT scans, aberrant hyperreflectivity was present in the outer retina and ONL thinning was observed. In FAC-injected Abca4–/– mice with pronounced RPE bisretinoid lipofuscin accumulation, the hyperautofluorescent puncta were more abundant than in the wild-type mice, and the extent of ONL thinning was greater. Conversely, the intravitreal injection of FAC in Mertk–/– mice led to a more modest increase in A2PE after 2 days. In contrast to the effect of iron accumulation, chelation with DFP resulted in significantly increased levels of A2E and A2-GPE and qAF due to the reduced iron-catalyzed oxidation of bisretinoids. In Mertk–/– mice, the A2E level was significantly lower and the ONL area was smaller than in DFP-treated mice. DFP chelation did not impair the visual cycle in BALB/cJ mice.ConclusionIron accumulation was associated with progressive impairment in photoreceptor cells that was associated with the increased formation of a bisretinoid species known to form in photoreceptor outer segments as a precursor to A2E. Additionally, disease features such as the development of hyperautofluorescence puncta in fundus AF images, hyperreflectivity in the outer retina of SD-OCT scans, and ONL thinning were more pronounced when iron was delivered to Abca4–/– mice with a greater propensity for bisretinoid formation. Higher bisretinoid levels and enhanced qAF are indicative of lesser bisretinoid loss due to oxidation.